La cátedra de bibliografía de la Universidad Complutense de Madrid - Clemente San Román, Yolanda (Revista General de Información y Documentación, 2007)
The article offers a panoramic view of the evolution of Bibliography as a scientific discipline in the University. Parting from the origins in the mid-nineteenth century, in the context of the Higher School of Diplomacy, it studies the incorporation of the discipline in the Complutense University, the periods of decadence and the moments of splendour starting in the 1970s, before ending with a presentation of the current state of the discipline, both as a subject in the classroom and in the field of research. Special attention is given to the outstanding moments of this history, as well as to the most important achievements and to the influence of bibliography outside the Philology Faculty of Madrid’s Complutense University.